Numerical investigation of vortex induced vibration of a circular cylinder for mass ratio less than 1.0. (1st May 2022) - Liu, Mingming; Jin, Ruijia; Wang, Haocheng
Abstract: A two-dimensional (2D) numerical model was developed by solving the Reynolds Averaged Navier-Stokes Equations (RANS) with the SST k - ω turbulent model closure to investigate vortex induced vibration of a circular cylinder for mass ratio less than 1.0. The sensitivity analysis of the grid in the present numerical model was carried out firstly, then the comparisons between the numerical results and the published experimental results were shown to validate the numerical model, and good achievement was obtained. In this study, the elastically supported circular cylinder with mass ratio less than 1.0 was only allowed to move in the cross-flow direction. The fluid forces on the circular cylinder and the motion response were studied. It can be seen from the numerical results that the mass ratio has great effect on the fluid force and the vibration amplitude, especially on the "lock-in" region for the circular cylinder with mass ratio less than 1.0. Highlights: A two-dimensional numerical model is developed to study vortex induced vibration of a circular cylinder for mass ratio less than 1.0 The effect of mass ratio on the process of vortex induced vibration is investigated. The structure can be regard as a submerged floating tunnel.